2014
DOI: 10.1038/ncomms5574
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the frequency and bias of stochastic switching to control phenotypic variation

Abstract: Mechanisms that control cell-to-cell variation in gene expression ('phenotypic variation') can determine a population's growth rate, robustness, adaptability and capacity for complex behaviours. Here we describe a general strategy (termed FABMOS) for tuning the phenotypic variation and mean expression of cell populations by modulating the frequency and bias of stochastic transitions between 'OFF' and 'ON' expression states of a genetic switch. We validated the strategy experimentally using a synthetic fim swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…Several examples have shown that the noise in gene expression is a potential mechanism to generate phenotypic heterogeneity [ 27 , 49 , 58 ]. The phenotypic diversity has been a focus of attention in biology, since the amount of phenotypic variation (also known as gene expression noise) in a cell population can determine fitness by affecting growth rate, robustness and adaptation [ 28 - 31 ]. Population diversity offers an alternate way that cells adapt to randomly fluctuating environments [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several examples have shown that the noise in gene expression is a potential mechanism to generate phenotypic heterogeneity [ 27 , 49 , 58 ]. The phenotypic diversity has been a focus of attention in biology, since the amount of phenotypic variation (also known as gene expression noise) in a cell population can determine fitness by affecting growth rate, robustness and adaptation [ 28 - 31 ]. Population diversity offers an alternate way that cells adapt to randomly fluctuating environments [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing phenotypic variation is particularly beneficial to organisms that need to adapt efficiently to sudden changes in chemical composition, local temperature, or illumination [ 30 ]. In contrast, decreasing phenotypic variation is usually advantageous in constant environments [ 28 , 37 , 38 ]. The peaks of gene product distribution are a cause of generating phenotypic diversity in genetically identical cell populations [ 27 ], and the gene product noise always decreases with the increase of the leakage rate as shown above, so we naturally consider the relationship between promoter leakage and phenotypic selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides allowing the quantification of intrinsic and extrinsic variation, our experimental platform can be used to study the phenotypic consequences of gene expression variability by artificially altering the endogenous variation levels of genes of interest 36,37 . Moreover, by regulating all cellular outputs to the same target levels, our integral feedback controllers effectively "cancel out" the effect of slowly-varying sources of extrinsic variation.…”
Section: Discussionmentioning
confidence: 99%
“…A system with such properties has only been described in bacteria by modulating bias and frequency of a genetic switch. 29 …”
mentioning
confidence: 99%